TIPS AND TRICKS FOR WRITING A SCIENTIFIC ARTICLE - van Dijk, P. Assoc. Prof. Jitse (Profese Online, 2013)
In this manuscript some writing tips and tricks are offered which can be of help in the process of creating a convincing and readable manuscript. The process of writing a manuscript itself should become easier, in particular for the inexperienced writer, with help of the websites mentioned in this article.
Keywords: scientific article; writing